Reviewing the Success of the Keluarga Sakinah Program: The Urgency of Evaluation for more Accurate Policies - Rohani, Rohani (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper evaluates the implementation of the Keluarga Sakinah (Harmonious Family) program, which has not yet optimally achieved its goals due to various policy problems. The main issue identified is the lack of a uniform implementation standard, exacerbated by a weak monitoring and accountability mechanism. This situation stems from the absence of a comprehensive guideline, a standardized curriculum, and clear performance indicators. Methodologically, this study uses a qualitative policy analysis approach, adapting the stages of analysis from William N. Dunn's model. Secondary data from policy documents, academic publications, and government reports were used to identify the problems, analyze their root causes, and evaluate alternative solutions. A USG (Urgency, Seriousness, Growth) analysis was applied to prioritize the issues, while Dunn's alternative scoring was used to select the best solution. The findings indicate that standardizing the curriculum and guidance modules is the most effective alternative. Therefore, it is recommended that the Minister of Religious Affairs issue a new Ministerial Regulation to govern standardization, facilitator qualifications, and key performance indicators (KPIs). The innovation in this recommendation lies in the proposal to integrate an impact-based information management system to facilitate more adaptive and evidence-based supervision.